Photocatalytic and Antimicrobial Activities of Poly(aniline-co-o-anisidine)/Zinc Oxide Nanocomposite - Sivakumar1, K.; Senthil Kumar1, V.; Shim3, Jae-Jin; Haldorai3, Yuvaraj (Asian Journal of Chemistry, 2014)
The conjugated poly(aniline-co-o-anisidine)/zinc oxide [poly(Ani-co-oAs)/ZnO] nanocomposite was prepared by in-situ chemical oxidative polymerization of comonomers with ZnO nanoparticles and applied as a photocatalyst for the degradation of methylene blue dye. Scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy and UV-visible spectroscopy measurements were used to characterize the resulting pure copolymer and nanocomposite. Transmission electron microscopy analysis showed that the nanoparticles with amean diameter of 15-25 nm were dispersed in the copolymer matrix. Thermogravimetric analysis indicated that the nanocomposite had a higher decomposition temperature than the pure copolymer. The conductivity measurements showed the resulting nanocomposite possessed higher conductivity as compared to the pure copolymer. The photocatalytic activity results indicated the degradation of methylene blue dye by 97 % over the surface of nanocomposite catalyst under UV-irradiation for 3 h. The nanocomposite exhibited good antimicrobial activity against the microbial species and the clear zone diameter of the microbial inhibition is correlated to the antimicrobial activity of nanocomposite.